2010
DOI: 10.1016/j.trstmh.2009.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Human leptospirosis in Croatia: current status of epidemiology and clinical characteristics

Abstract: This study presents the current status of human leptospirosis in Croatia from an epidemiological and clinical viewpoint. Data from annual reports of the Croatian Institute for Public Health as well as archives of the University Hospital for Infectious Diseases 'Dr Fran Mihaljevic' (UHID) in Zagreb were used in this retrospective cohort analysis. The mean yearly incidence of leptospirosis from 1990 to 2007 was 1.83/100 000 inhabitants, with an incidence >2.5/100 000 inhabitants recorded approximately every 3-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
5
11
0
Order By: Relevance
“…The Philippine post‐flood outbreak generated 2,299 local cases and 178 (case fatality rate 8%) deaths (Amilasan et al, ). In China, most leptospirosis cases typically occur in summer and autumn, which are consistent with reports from countries in both temperate and tropical zones (Slack, Symonds, Dohnt, & Smythe, ; Topic et al, ). In temperate climates, the rates of leptospirosis are in the range of 0.1–1 per 100,000 per year, while these rise to 10–100 in the tropics during normal endemic periods; epidemics in tropical, wet regions often see infection rates greatly exceeding 100 per 100,000 (Sakundarno et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…The Philippine post‐flood outbreak generated 2,299 local cases and 178 (case fatality rate 8%) deaths (Amilasan et al, ). In China, most leptospirosis cases typically occur in summer and autumn, which are consistent with reports from countries in both temperate and tropical zones (Slack, Symonds, Dohnt, & Smythe, ; Topic et al, ). In temperate climates, the rates of leptospirosis are in the range of 0.1–1 per 100,000 per year, while these rise to 10–100 in the tropics during normal endemic periods; epidemics in tropical, wet regions often see infection rates greatly exceeding 100 per 100,000 (Sakundarno et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Based on previous reports the gender ratio for leptospirosis in Albania goes as high as 1:8 in favour of the males [3]. Although different studies have shown different ratios, there is a major body of literature that demonstrates a higher incidence of leptospirosis in males worldwide [16][17][18][19][20][21][22][23][24][25][26][27][28]. The goal of this study is in four points: to give some data and to share our experience with human leptospirosis in Albania; to describe the prevalence regarding to the role of gender in the prevalence of human leptospirosis; to make a gender specific analysis of the clinical manifestations in patients diagnosed and treated for leptospirosis in our infectious diseases service during January 2005-December 2016 period and to do a review of literature related to this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…With a mean yearly infection incidence of 1.7 per 100,000 inhabitants, Croatia has one of the highest recorded incidences of human leptospirosis in the world. 1 Borrelia infections result in two distinct tick-transmitted diseases, Lyme borreliosis and relapsing fever (RF). Both are endemic in Croatia with majority of cases of borreliosis reported in the northwest of the country.…”
Section: Introductionmentioning
confidence: 99%